2010
DOI: 10.1007/s11355-010-0144-x
|View full text |Cite
|
Sign up to set email alerts
|

Wetland restoration to enhance biodiversity in urban areas: a comparative analysis

Abstract: Wetlands mitigation for any activity can be applied to avoid or minimize damage and restore, enhance, or create wetlands as well. New tools for mitigating and creating wetlands are available, including the Wetland Impact Assessment. This article explores many current issues in wetland mitigation and mitigation strategies, using case studies for illustration. We include some general guidelines for successful wetland mitigation based primarily on existing literature review in several cities. We use comparison an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Recently, restoration and reconstruction of artificial habitats for aquatic life have been ongoing in the urban freshwater system in Korea . Accordingly, wetland assessment, planning, restoration design, construction oversight, and ecological monitoring based on fauna have been considered . Though the water quality of the urban freshwater system has been managed based on physicochemical parameters, there was no consideration of water quality based on biological safety for aquatic organisms including amphibians.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, restoration and reconstruction of artificial habitats for aquatic life have been ongoing in the urban freshwater system in Korea . Accordingly, wetland assessment, planning, restoration design, construction oversight, and ecological monitoring based on fauna have been considered . Though the water quality of the urban freshwater system has been managed based on physicochemical parameters, there was no consideration of water quality based on biological safety for aquatic organisms including amphibians.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that fragments with larger areas and higher aquatic vegetation heterogeneity contained more waterbirds; however, this remains an indecisive guide for wetland managers when setting the least area criterion of constructed wetlands. Therefore, combined with the requirement for stormwater runoff (Malaviya and Singh, 2012 ) or pollution abatement efficiency (Nivala et al., 2018 ), wetland construction must integrate more ecosystem services (Kim et al., 2011 ). For improved waterbird conservation, we suggest that future studies should aim to quantify the appropriate wetland area, according to waterbird composition characteristics and their life history, to determine the smallest area necessary for constructing artificial wetlands in given regions (Garrett‐Walker et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The water environment has been polluted with heavy eutrophication and significant nitrogen, and the water resources have decreased. Based on these factors, the Qilihai Wetland national nature reserve should be managed by the appropriate administrative department within the provincial people’s government or under the State Council [ 39 ]. All units and individuals should be obligated to protect nature resources in Qilihai Wetland, and the government should have the right to report and prosecute any unit or individual that has destroyed or occupied the reserve.…”
Section: Methodsmentioning
confidence: 99%